Surprising feedback improves later memory - Fazio, Lisa K. (2009)
The hypercorrection effect is the finding that high-confidence errors are more likely to be corrected after feedback than are low-confidence errors (Butterfield & Metcalfe, 2001). In two experiments we explored the idea that the hypercorrection effect results from increased attention to surprising feedback. In Experiment 1, participants were more likely to remember the appearance of the presented feedback when the feedback did not match expectations. In Experiment 2, we replicated this effect using more distinctive sources, and also demonstrated the hypercorrection effect in this modified paradigm. Overall, participants better remembered both the surface features and the content of surprising feedback.